1996
DOI: 10.1002/eji.1830260606
|View full text |Cite
|
Sign up to set email alerts
|

Structure and chromosomal location of the mouse interleukin‐12 p35 and p40 subunit genes

Abstract: Interleukin-12 (IL-12) is a heterodimeric cytokine composed of p35 and p40 subunits and is required for induction of T helper 1 (Th1) responses. Knowledge of how the IL-12 gene is regulated will permit an understanding of susceptibility and resistance to pathogenic microbes and to autoiummune diseases. In this report, we provide the gene structures, nucleotide sequences and chromosomal assignment for the p35 and p40 subunits of mouse IL-12. The p35 and p40 subunit genes are distributed over 8 kb and 14 kb, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 22 publications
4
62
0
Order By: Relevance
“…A typical TATA box, TATAAAA is located at Ϫ30 to Ϫ24, indicating that transcription of IL-10 is regulated by a TATA-type promoter as are many other cytokine genes, although not all (e.g., IL-7 (33), IL-12 p35 (34,35), and IL-18 (36) genes). We have also demonstrated that IL-10 gene expression is regulated by transcription factors Sp1 and Sp3, which are known to be constitutively expressed and to bind to the G ϩ C-rich consensus sequence (GC box).…”
Section: Discussionmentioning
confidence: 99%
“…A typical TATA box, TATAAAA is located at Ϫ30 to Ϫ24, indicating that transcription of IL-10 is regulated by a TATA-type promoter as are many other cytokine genes, although not all (e.g., IL-7 (33), IL-12 p35 (34,35), and IL-18 (36) genes). We have also demonstrated that IL-10 gene expression is regulated by transcription factors Sp1 and Sp3, which are known to be constitutively expressed and to bind to the G ϩ C-rich consensus sequence (GC box).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the IL-12 p40 subunit is highly inducible and is regulated primarily at the transcription level [17,36]. Expression of IL-12 p35 is also subject to similar regulation, although to a much lesser extent than p40 [17,35,37,38]. As production of IL-12 protein in THP-1 cells was below the detection level, we only examined the effect of redox status on IL-12 p40 mRNA production in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…No T1D susceptibility gene has as yet been mapped to the vicinity of Il12b in backcrosses of NOD mice with B6 19,20 or F2 crosses to NOR. 18 For example, the Idd4 gene 19 is on mouse chromosome 11 but was mapped to a region over 20 cM distal to the reported location 14 of Il12b. However, the B6 backcrosses would not have detected a NOD-dominant gene effect, while in the NOR crosses a potentially protective effect of the NOR allele may not be sufficiently strong to be detected in the presence of all the other susceptibility alleles shared between the NOD and NOR strains.…”
Section: Discussionmentioning
confidence: 99%
“…13 In view of the importance of IL-12p40 in the regulation of the immune response, and in T1D in particular, we sequenced the cDNA from Il12b of the NOD mouse and compared it with the published IL-12p40 sequences, which are exclusively from the C57BL/6 strain. 3,14 We found polymorphisms in the IL-12p40 sequence shared by NOD and other autoimmune-prone strains, one of which resulted in an amino acid substitution that caused the loss of an epitope recognized by a monoclonal antibody. We also observed allele-specific effects on basal and stimulated production of IL-12p40.…”
Section: Introductionmentioning
confidence: 94%